Analiza nawigacyjna: uczestnictwo w kulturze jako tworzenie życia - Rapior , Waldemar (Człowiek i Społeczeństwo, 2013)
Inspired by the research project entitled “Creating Culture. A Study of Participation in Culture” which I was co-creator, I aim at showing the methodology of building the bottom-up archive, and how can we use such an archive for the sociological purpose.